Budgetary policy of the European Communities: Squaring the circle - Gerhard Stahl (Intereconomics, 1983)
The EC's budgetary problems are coming to a head. For 1983 virtually all the Community's resources have been utilized, and there are growing fears that the Community will soon have to declare itself bankrupt unless changes are made to current policy. What should be done to secure the financing of Community policies taking account of the additional financial requirements resulting from the impending accession of Spain and Portugal?
Keywords: 330; EC